Environmental management of tourist activity in the southern Amazon region - Iglesias, Silvia (2011)
The research study propose the environmentalmanagement of the tourist activities in the upper side of the Uctubamba river, located in the provinces of Luya and Bongará, Amazon Region, specifically, for the tourist destinations of the Kuelap’s Fortress and the Gocta’sWaterfall. The main objectiveswere to proceed with the environmental diagnosis in the tourist destinations of Kuelap’s Fortress and the Gocta’s Waterfall, identifying theenvironmental impacts due to tourism, and finally present an Environmental Management Plan. Among the main proposals of environmental management are included the implementation of suggested environmental policy, the soil quality’s management and the archeologist and tourists’ resources.